Does constitutionalizing economic and social rights promote their fulfillment?. Issue 4 (1st October 2016) - Kaletski, Elizabeth; Minkler, Lanse; Prakash, Nishith; Randolph, Susan
ABSTRACT: This article explores whether constitutional provisions promote fulfillment of economic and social rights. This is accomplished by combining unique data on both enforceable law and directive principles with the Social and Economic Rights Fulfillment Index (SERF Index), which measures government fulfillment of such rights. The results indicate that there is a positive and significant correlation between enforceable law provisions and the right to health and education components of the SERF Index. The strongest relationship appears to be for the right to health component where the inclusion of an enforceable law provision on economic and social rights in the constitution is correlated with an increase in the health component by 9.55, or 13.0%, on average. These results support the idea that constitutional provisions may be one way to improve economic and social rights outcomes.